2009
DOI: 10.1121/1.3097469
|View full text |Cite
|
Sign up to set email alerts
|

Relations between frequency selectivity, temporal fine-structure processing, and speech reception in impaired hearing

Abstract: Frequency selectivity, temporal fine-structure (TFS) processing, and speech reception were assessed for six normal-hearing (NH) listeners, ten sensorineurally hearing-impaired (HI) listeners with similar high-frequency losses, and two listeners with an obscure dysfunction (OD). TFS processing was investigated at low frequencies in regions of normal hearing, through measurements of binaural masked detection, tone lateralization, and monaural frequency modulation (FM) detection. Lateralization and FM detection t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

59
265
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(339 citation statements)
references
References 95 publications
(92 reference statements)
59
265
10
Order By: Relevance
“…1). This tendency is consistent with previous studies (e.g., Strelcyk and Dau 2009;Moore and Sek 1996). DPOAEs were lowest at lower frequencies and reached a maximum around 1 kHz and gradually decreased with increasing frequency above 1 kHz (Fig.…”
Section: Comparison With Previous Studiessupporting
confidence: 94%
See 3 more Smart Citations
“…1). This tendency is consistent with previous studies (e.g., Strelcyk and Dau 2009;Moore and Sek 1996). DPOAEs were lowest at lower frequencies and reached a maximum around 1 kHz and gradually decreased with increasing frequency above 1 kHz (Fig.…”
Section: Comparison With Previous Studiessupporting
confidence: 94%
“…This interpretation is consistent with earlier findings that hearing-impaired listeners, who tend to show decreased DPOAE levels (e.g., Dorn et al 1999), exhibit deficits in FM detection tasks (Lacher-Fougere and Demany 1998;Moore and Skrodzka 2002;Strelcyk and Dau 2009). This interpretation, however, might appear to be inconsistent with the present study and the study of hearingimpaired listeners published by Strelcyk and Dau (2009), which showed no significant correlation between FMDLs and hearing level. Several studies reported a correlation between hearing level and DPOAE level (e.g., Dorn et al 1999).…”
Section: Interpretation Of the Regression Coefficientssupporting
confidence: 92%
See 2 more Smart Citations
“…Recent perceptual studies focused on temporal coding have suggested that envelope cues are most salient for understanding speech in quiet (Shannon et al 1995) and fine-structure cues are most important for speech in noise (Qin and Oxenham 2003;Zeng et al 2005). Listeners with SNHL appear to have reduced ability to use fine-structure cues for both speech and non-speech stimuli (Buss et al 2004;Lorenzi et al 2006;Hopkins and Moore 2007), and this deficit does not depend on reduced frequency selectivity (Lorenzi et al 2009;Strelcyk and Dau 2009). In contrast, envelope coding is generally believed to be unaffected by SNHL.…”
Section: Introductionmentioning
confidence: 99%